Digital Marketing Strategy for Promoting Grab food at Ratu Penyet Niaga, a Small and Medium Enterprise in Karawang - Alli Pujaswati; Enjang Suherman; Laras Ratu Khalida (Jurnal Indonesia Sosial Sains, 2026)
This study aims to examine the digital promotion methods used by the Ratu Penyet Niaga Karawang MSME through the GrabFood application. The study used a descriptive qualitative approach with a weighted SWOT analysis method through the preparation of the IFAS and EFAS matrices. Data collection was carried out through in-depth interviews with business owners, direct observation, documentation, and analysis of consumer reviews on the GrabFood platform. The study shows that the Ratu Penyet Niaga Karawang MSME is in the Advantages–Opportunities (S–O) quadrant, indicating that this business has strong internal strengths and also has significant opportunities in the digital market. Therefore, the recommended strategy is a growth strategy by maximizing product quality, distinctive taste, speed of service, and utilizing GrabFood promotional features. Promotion integration through social media and support for MSME digitalization programs are important factors in creating sustainable digital promotions. This study shows that the success of digital promotions for small and medium enterprises depends not only on the platform chosen, but also on the business owner's ability to manage internal resources and respond intelligently to market opportunities.